Interconnections in the education–migration–labor market chain in Central and Eastern Europe - Naila Mukhtarova; Roza Nurtazina; Dariusz Krawczyk; Veronika Barvinok; Anna Vorontsova; Sergej Vasić; Tetiana Vasylieva (Problems and Perspectives in Management)
This study examines the interconnections between transformations in the education sphere, migrations waves, and labor market in 2000–2021 based on a panel data set for 14 Central and Eastern European countries (7 – former members of the Council for Mutual Economic Assistance; 5 – former republics of the USSR, and 2 – former republics of Yugoslavia). Statistical data were collected from the World Bank, the Organisation for Economic Cooperation and Development, and the International Labour Organization databases. To describe this interconnection, a pool of parameters was formed. Those that cause the greatest variability were selected using exploratory factor analysis: for education – the number of teachers and students in higher education and public spending on education; for migration – the net migration flow, personal remittances sent and received; for labor market –unemployment rate and the share of highly educated people among the employed. Confirmatory factor analysis identified the most influential determinants: for education – the number of students in higher education; for migration – paid personal remittances; for labor market – unemployment rate. The covariance analysis demonstrated a robust direct correlation between education and migration (positive shifts in the education sector serve as a catalyst for pursuing superior employment opportunities or continuing education abroad). A relatively weak direct correlation was between education and the labor market (a more highly educated workforce has only a limited impact on the structure and dynamics of the labor market). Finally, a moderate inverse correlation was between migration and the labor market (deteriorating labor market conditions give rise to migration waves). AcknowledgmentThis study is funded in terms of the projects “Business-Education-Science” Coopetition: Institutional and Economic Models of Innovation Transfer for National Security and Sustainable Development (№ 0122U000772) and “Modelling educational transformations in wartime to preserve the intellectual capital and innovative potential of Ukraine” (№0123U100114).